Comparative analysis of salivary microbiota in diabetic and non-diabetic individuals of North India using metagenomics - Jyotsana Agarwal; Pragya Pandey; Shailendra K. Saxena; Swatantra Kumar (Elsevier, 2024)
Background: Saliva, an oral secretion is considered an essential biological modulator involved in maintaining oral homeostasis. Increased glucose levels in diabetic patients' saliva may have an impact on diversity of microbes. Comparing the salivary microflora of diabetic and non-diabetic cohorts will help in diagnosis and risk assessment of oral health complications. This will provide greater knowledge about the contribution of oral microbes to the development of oral illnesses. The association between salivary microbiota and diabetic state is less explored in the North Indian population, hence current observational study was performed to analyze the salivary microflora of diabetic and non-diabetic individuals using metagenomic analysis. Materials and methods: This single-center non-randomized observational trial was conducted in Uttar Pradesh, India. Participants were enrolled into either diabetic (n = 68) or non-diabetic groups (n = 68) based on their diabetes status. Following saliva collection, DNA was extracted and metagenomic sequencing was performed. Results: Phylum Bacteroidetes and Fusobacteria were significantly abundant in diabetic individuals (p < 0.0001), while Proteobacteria was significantly higher among non-diabetic individuals (p < 0.0001). No statistical difference in phylum Actinobacteria and Firmicutes among diabetics and non-diabetics. Veillonella, Prevotella, Porphyromonas, Leptotrichia, Lactobacillus, and Streptococcus were greater in diabetics whereas the abundance of Capnocytophaga and Neisseria was more among non-diabetics (p < 0.05). Conclusions: The genera Veillonella, Prevotella, Porphyromonas, Leptotrichia, Lactobacillus, and Streptococcus were comparatively over the odds with the diabetics in India. The association between microbiota in diabetic population and risk related to increase in occurrence of caries, gingivitis, and periodontitis in diabetic population prevalence should be investigated.